The case of the great elephant escape - Doolittle, June (HarperEntertainment New York, 1999)
Mary-Kate and Ashley's new friend Lakeisha is a young circus performer who rides on the back of a tiny elephant named Baby Maysie. But when someone elephant-naps Baby Maysie, it is up to the Trenchcoat Twins to solve this gigantic crime before show time!